Modelos in vitro para el desarrollo de una acuicultura sustentable. La aplicación del modelo de líneas celulares - Olivares-Ferreti, Pamela (2025)
In vitro models are widely used in various disciplines, allowing more tests to be performed in less time. Within biotechnology, cell models play a prominent role. In this article, we review cell lines' usefulness and versatility in aquaculture, focusing on their applications in nutrition, health and environmental assessment. It shows how using cell lines can provide enlightening results, reducing both the time and costs of testing and increasing the diversity of experiments that can be performed. In the aquaculture industry, there is a constant challenge to improving diets through the use of additives and understanding the mechanisms of action of each compound. These processes are not commonly observed in vitro or in cellular models. Although the development of aquaculture cell lines applied to the analysis of feed supplements or feed treatments is still developing, in recent years, this model has been introduced for the screening of molecules, pharmacological studies and description of some mechanisms of action, offering preliminary results for the development of diets or more extensive in vivo studies over time. However, achieving its use as a preliminary tool for generating sustainable aquaculture practices remains a significant challenge. Cell lines represent a multifaceted tool in aquaculture, providing information on the effects of new molecules incorporated into the production industry.